A HELIXOL‐Derived Bisphosphinite Ligand: Synthesis and Application in Gold‐Catalyzed Enynes Cycloisomerization. Issue 11 (5th February 2019) - Medena, Caleb; Calogero, Francesco; Lemoine, Quentin; Aubert, Corinne; Derat, Etienne; Fensterbank, Louis; Gontard, Geoffrey; Khaled, Omar; Vanthuyne, Nicolas; Moussa, Jamal; Ollivier, Cyril; Petit, Marc; et al.
Abstract : The synthesis, optical resolution through derivatization, characterization, and utilization of a new helical bis(phosphinite gold) complex derived from HELIXOL are described. By using an efficient cobalt catalyst, neither irradiation nor high catalytic loading was required to access the helicene of interest. The latter was phosphorylated to afford a new chiral ligand that was studied. Especially, treatment with AuCl(SMe2 ) gives a dinuclear gold complex that was used in cycloisomerization reactions. Abstract : The synthesis, optical resolution through derivatization, characterization and utilization of a new helical bisphosphinite–gold complex derived from HELIXOL are described.